Frying pressure and temperature effects on sensory characteristics of coated chicken nuggets - Salma Mohamad Yusop; Mohamad Yusof Maskat; Wan Aida Wan Mustapha; Aminah Abdullah (Universiti Kebangsaan Malaysia, 2009)
A study was carried out to evaluate the effects of frying pressure (102 and 156 kPa) and temperature (150, 165 and 180°C) on sensory characteristics of chicken nuggets coated with wheat, rice and sago flours. Batters from wheat, rice and sago flours were prepared by mixing each flour with water at a weight ratio of 1:1.2 (flour: water). Chicken nuggets were dipped in the prepared batters and fried at the different pressure and temperature for 7 minutes. Sensory evaluation was done using trained panelists (n=7) with two replication. Attributes assessed were color, aroma, coating thickness, adhesiveness, hardness, crispness, oiliness, juiciness and overall acceptance. Results showed that using different frying pressures and temperatures did significantly affect (p<0.05) all the sensory attributes of chicken nuggets coated with wheat, rice and sago flours. It was observed that coated chicken nuggets fried at a pressure of 156 kPa and temperature of 165°C was most preferred by the trained panellists.